A study to establish the prevalence of urinary tract infection in preterm labour - Kruthipati, Rashmi; Chethan, Radhika; Shiva, Anitha Gabbalkaje; Suresh, Sukanya; Krishnappa, Tejeswini Kolige (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Urinary tract infection (UTI) is one of the many etiological factors of preterm labour. Preterm labour is the onset of labour after 28 weeks and before 37 weeks of gestation. Preterm labour is a significant cause for perinatal morbidity and mortality. Hence early diagnosis and management of etiological factors is necessary. The most common bacterial infection encountered during pregnancy is UTIs. Early detection and management of UTIs may effectively prevent complications of preterm labour including preterm birth. Aims and objectives of the study was to estimate the prevalence of UTIs in preterm labour. Methods: cross sectional study with a total of 250 patients carried out in the department of obstetrics and gynaecology, Vanivilas hospital, BMCRI for a period of 6 moths-Aug 2019-Feb 2020. Patients in preterm labour i.e., cervical dilatation ≥1 cm, cervical effacement ≥80% with true labour pains were included in the study after taken informed consent form the patient. Detailed clinical history including age of patient, level of education, duration of antenatal care, parity, and obstetrical history was taken. Gestational age was calculated by LMP or early ultrasound. General examination, systemic examination and obstetric examination was done. Routine investigations were done along with clean catch midstream urine sample in a sterile container. Two samples were collected: 1st sample for microscopic examination, 2nd sample for culture and sensitivity. Conclusions: Untreated UTI can be associated with obstetric complications. The most common bacterial infection during pregnancy is UTIs. All women should be screened for UTI at the first antenatal visit. Once diagnosed it should be promptly treated with suitable antibiotic which is sensitive yet safest.